A Case Report of Allergic Contact Dermatitis due to Mandragora Radix - Sevim Baysak; Müzeyyen Gönül; Damla Atacan; Can Ergin (Case Reports in Immunology)
An 82-year-old male presented with rash, burning, and itching on his knees that had started 4 days after the local application of Mandragora Radix sap for 3 consecutive days. A dermatological examination revealed erythematous, edematous, and scaly plaque lesions on the patient’s knees. An open application test with M. Radix was performed, and the patient was diagnosed with allergic contact dermatitis due to M. Radix. Mandragora species, which belong to the Solanaceae family, have sedative, aphrodisiac, emetic, analgesic, and anesthetic properties. To the best of our knowledge, only one case of M. Radix-induced allergic contact dermatitis has been previously reported.